Registros em fragmentos: uma memória em construção - Cosenza, Monique Ferruccio (2021)
This work presents a construction of a visual memory proposal, from three years of photographic records, in the Occupation Solano Trindade, an urban occupation, of the National Movement of Struggle for Housing in Rio de Janeiro. For this, it rescues the origin of the photographic relevance as an academic product, discusses material culture concepts, problematizes the researcher's relationship with his own photographic work and exposes the visibility importance of spaces for struggle in Brazil.Também disponível on-line.